2021
DOI: 10.3390/molecules26092657
|View full text |Cite
|
Sign up to set email alerts
|

Nipagin-Functionalized Porphyrazine and Phthalocyanine—Synthesis, Physicochemical Characterization and Toxicity Study after Deposition on Titanium Dioxide Nanoparticles P25

Abstract: Aza-porphyrinoids exhibit distinct spectral properties in UV-Vis, and they are studied in applications such as photosensitizers in medicine and catalysts in technology. The use of appropriate peripheral substituents allows the modulation of their physicochemical properties. Phthalocyanine and sulfanyl porphyrazine octa-substituted with 4-(butoxycarbonyl)phenyloxy moieties were synthesized and characterized using UV-Vis and NMR spectroscopy, as well as mass spectrometry. A comparison of porphyrazine with phthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The fluorescence studies performed for the DMF and DMSO solutions of Pz 4 did not reveal any emission properties. The literature data indicated that emission quenching by sulfur atoms combined with the porphyrazine core could be a reason for the lack of fluorescence [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence studies performed for the DMF and DMSO solutions of Pz 4 did not reveal any emission properties. The literature data indicated that emission quenching by sulfur atoms combined with the porphyrazine core could be a reason for the lack of fluorescence [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hybrid material was photocatalytically active and degradation of both substances was noted after irradiation with red light for 8 min [165]. In another study with nipagin-functionalized porphyrazines, phthalocyanines, and P25 TiO 2 , fluorescence and singlet oxygen quantum yields as well as photostability were assessed [166]. The measurements were conducted based on the reduction in DPBF in DMF and DMSO after irradiation with red light (665 nm).…”
Section: Porphyrinoids and Titanium(iv) Oxide-based Hybrid Materials And Their Photocatalytic Activitymentioning
confidence: 99%
“…The materials showed considerable dark toxicity-up to 80% decrease in cell viability, reaching nearly 100% after irradiation of the samples with red light. Due to this activity, the usage of these compounds in photodynamic antibacterial studies could be considered [166].…”
Section: Porphyrinoids and Titanium(iv) Oxide-based Hybrid Materials And Their Photocatalytic Activitymentioning
confidence: 99%